Vaginal cuff dehiscence and post surgical evisceration: case report - Alarcón-Gutiérrez, Javier (2021)
Vaginal cuff dehiscence is the premature separation of the sutured vaginal incision, which in 70% of the cases manifests with evisceration of intestinal loops through the vaginal canal. Among its risk factors, age and alterations in the postoperative hysterectomy site stand out. The diagnosis is made by means of an adequate physical examination and the treatment, purely surgical, involves the return of the intestinal viscera and correction of the dehiscence. We describe the case of a 50-year-old woman who presented dehiscence of the vaginal vault with evisceration of a portion of the distal ileum, who underwent surgical and pharmacological treatment.